Mobile info-communication systems and wireless 5G and 6G technologies - Tresor, M. A. (ХНУРЕ, 2019)
This work is about the Wireless communication technologies Generation which is grown, advanced significantly in the mobiles telecommunications systems and networks
Keywords: NGN; 5G; 6G